Business Strategy Innovation Based on Business Model Canvas (BMC) Case Study of Underpriced Skincare Store - Rahmadani, Sagina; Haryadi, Haryadi (Holistic Science, 2025)
This study aims to design innovative business strategies using the Business Model Canvas (BMC) approach for an underpriced skincare store in Medan. A descriptive qualitative approach was used to identify the store's strengths, weaknesses, opportunities, and threats through a SWOT analysis integrated into the nine BMC elements. Research data was obtained through in-depth interviews with the owner, employees, suppliers, and customers. The results show that the store has advantages in competitive prices, responsive service through the role of beauty advisors, and the presence of multiple digital sales channels. However, limitations were found in the absence of a Customer Relationship Management (CRM) system and dependence on a single e-commerce platform, which are strategic concerns for future business development. Recommended strategic innovations include developing a customer loyalty system, utilizing the TikTok Shop platform, and diversifying market segments. The implementation of BMC accompanied by a SWOT analysis has been proven to produce relevant, adaptive, and sustainable strategic alternatives to improve business performance.